Palestinian prisoners: a question of conscience. Edited By John Calhoun andRanjan Solomon. Geneva: The World Council of Churches, 2015, Pp. 107, ISBN: 978-2-8254-1653-2 - Abdel Salam, El Fatih Abdullahi (Bangladesh Institute of Islamic Thought (BIIT), Dhaka, 2015)
This resource book is published in conjunction with the World Week for Peace in Palestine Israel (WWPPI), an initiative of the Palestine-Israel Ecumenical Forum of the World Council of Churches. It is based on the topic of Palestinian prisoners and the theme explored in the last year, “Let my people go.” The choice of the theme clearly underscores the crisis that affects several thousand Palestinians and their families.